2007
DOI: 10.1016/j.urology.2007.04.048
|View full text |Cite
|
Sign up to set email alerts
|

Physiologic Reactivity to a Laboratory Stress Task Among Men with Benign Prostatic Hyperplasia

Abstract: Objectives-The sympathetic nervous system (SNS) and hypothalamic-pituitary-gonadal (HPG) axis are involved in the pathophysiology of benign prostatic hyperplasia (BPH). The SNS and HPG axis are also highly reactive to psychological stressors, yet associations between prostate function and reactivity to a psychological stressor have not been examined utilizing standardized psychological stress paradigms. The objective of this study was to examine associations between psychological stress reactivity and BPH dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 24 publications
0
19
0
1
Order By: Relevance
“…The relationship between the metabolic syndrome and LUTS may be based on the fact that the metabolic syndrome is associated with an overactivity of autonomic nervous system (Bjorntorp & Rosmond, 2000; Kasturi et al. , 2006; Ullrich et al. , 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between the metabolic syndrome and LUTS may be based on the fact that the metabolic syndrome is associated with an overactivity of autonomic nervous system (Bjorntorp & Rosmond, 2000; Kasturi et al. , 2006; Ullrich et al. , 2007).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study provided supporting evidence that stress conditions could be associated with the development and aggravation of prostatic disease. It was found that body mass index (BMI), age and greater diastolic blood pressure reactivity correlated with a greater transition zone volume, greater total prostate gland volume, greater post‐void residual bladder volume (RBV) and more severe LUTS (Ullrich et al. , 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Physiologic responses to a standardized laboratory stressor has also been associated with objective and subjective BPH disease parameters [9] .…”
Section: Introductionmentioning
confidence: 99%
“…Studies examining associations between physiologic measures of the ANS and LUTS are limited, but a few studies suggest that ANS activity may be associated with LUTS [5, 6]. However, the tests used in these studies were not specific for α -adrenergic or muscarinic acetylcholine function, making it difficult to determine whether specific ANS components are important in the development of LUTS.…”
mentioning
confidence: 99%
“…McVary et al [5] found associations between elevated urinary catecholamines, blood pressure readings, and heart rate measures following tilt-table testing and LUTS, prostate volume, and bother due to LUTS. Ullrich et al [6] also found associations between increases in diastolic blood pressure and cortisol following a laboratory stress test and prostate enlargement and LUTS. More recently, Choi et al [10] found that men with LUTS had lower measures of parasympathetic function compared to unaffected men.…”
mentioning
confidence: 99%